Community dance as a democratic dialogue. Issue 3 (April 2020) - Wise, Serenity; Buck, Ralph; Martin, Rose; Yu, Longqi
This article explores the values that bridge democracy and community dance. Policymakers show an interest in promoting democracy, including the very values shared between community dance and democracy. Observing this, we propose that policy may benefit from examining the pedagogy and practices of community dance, and incorporate relevant aspects of community dance's ability to teach democratic values, into education policy. Through personal accounts and references, it highlights the ways in which community dance could have democratizing effects on its participants, encouraging people to actively create inclusive, participatory, and empowering spaces. Democracy takes practice, and recent, ongoing violent events show us the need for greater civic education in society: education that disseminates the values of democracy, as well as the everyday work of practicing, supporting, and existing in a democracy. As community dancers, we are compelled to explore the ways in which our discipline might intersect with policy, and wider social and political issues. We approach this exploration by raising the question, how might community dance play a role in education policy, as a means of fostering democracy within our world? To address this question, we delve into our mutually held values of inclusion, participation, and empowerment, to further understand the ways they are apparent within the community dance field and the ways they are apparent in defining democracy. Serving as a starting point to larger discussions, we illustrate that democracy and community dance share certain values, that community dance has the potential to teach people how to embody these values, and that these values are conducive to education policy.